Pengembangan Pedagang Kue Melalui Networking di Kampung Kue Rungkut Lor, Kecamatan Rungkut Surabaya - Maria Widyastuti (Jurnal Pengabdian Barelang, 2020)
Surabaya has a community called "Pedagang Kue", in Kampung Kue precisely in the densely populated residential area, Rungkut Lor II, Rungkut District. The presence of the community of cake traders in the community originated from people's desire to obtain a better economic level, by making the cake village to economic activity, every morning, 65 cake sellers, mostly mothers, have sold various kinds of traditional cakes in front of their homes, but their efforts are still carried out individually and are not well organized, so the impact has not been seen significantly. So it is necessary to open a network with outside parties, among others, with the Daram Cendika Catholic University Community Service Team.The team makes programs that are currently needed, among others: Making SOPs so that work is more efficient, consistent and minimizes mistakes, simple bookkeeping in addition to being needed to know business development as well necessary instill understanding of the need for financial separation for business and personal needs costs. The public at large needs to know about the existence of a cake trader in a cake village, so we need a means of promotion that is by making brochures and katolok which aim to support the promotion tools that already existed before. The last program as a form of concern for the current situation is the corona virus outbreak, so the team and the residents of the cake village built a series of disinfecting sprinkle spray so that no residents were affected by the virus.